DEVELOPMENT OF E-MODULE SETS-BASED APPROACH ASSISTED WITH FLIP HTML5 MEDIA TO IMPROVE INDEPENDENT LEARNING AND LEARNING KNOWLEDGE OUTCOMES ON CHEMICAL EQUILIBRIUM MATERIAL - Norlaila Norlaila; Parham Saadi; Atiek Winarti; Leny Leny (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
The lack of utilization of resources is the main factor for the low level of student learning independence, yet in reality, teachers still struggle to connect chemical concepts with everyday life contexts. The SETS approach-based e-module is an innovation in enhancing students' learning independence and learning outcomes. This study aims to determine the validity and practicality of the developed chemistry learning module. This research and development was carried out to produce an e-module product based on the SETS approach assisted by flip HTML5 on chemical equilibrium material that is valid, practical, and effective in increasing independent learning and student knowledge learning outcomes. The development model used is a 4D model which consists of 4 phases, 1) Define, 2) Design, 3) Development, and 4) Disseminate. The purposive sampling technique was used as a sampling technique, namely students of class XI MIPA 1 at SMAN 10 Banjarmasin. Data collection techniques included questionnaires (validation sheets, product practicality, product effectiveness) and learning achievement tests. The results showed that the e-module: (1) is very valid with an average percentage of 90.98%, (2) is very practical, based on readability tests, response questionnaires, and observation sheets with an average score of 4.34, and (3) is effective in increasing learning independence and knowledge learning outcomes in terms of the N-gain learning independence of 0.45 in the medium category and the N-gain of knowledge learning outcomes of 0.71 in the high category. Based on the results obtained, it can be concluded that e-modules based on the SETS approach assisted by HTML5 flip media are appropriate for use in chemistry learning, especially in chemical equilibrium material.